A sealant for gaps in electrostatic chucks and its preparation method and application

By using a sealant containing silicone and modified nanosilicon dioxide, corrosion problems and high maintenance costs in the electrostatic suction cup gaps are solved, and higher corrosion resistance and longer service life are achieved.

CN117777941BActive Publication Date: 2025-03-14IC SEAL CO LTD

Patent Information

Application Number
CN202311562136.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-22
Publication Date
2025-03-14
Estimated Expiration
2043-11-22

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the corrosion problems and high maintenance costs in the gaps of electrostatic suction cups, especially when facing electrostatic suction cups from different manufacturers and models, gap size differences lead to complex sealing treatment.

Method used

Using a new sealant formulation, including silicone, modified nanosilicon dioxide and other fillers, sealant is prepared by blending and stirring, vacuum defoaming and centrifugation, and filled into the gaps in the electrostatic suction cup.

Benefits of technology

The sealant has excellent corrosion resistance and is suitable for gaps in various shapes and sizes, reducing the maintenance cost of electrostatic suction cups, extending service life, and improving the protection effect of the adhesive layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117777941B_ABST
    Figure CN117777941B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of semiconductor material technology, and in particular to a sealant for electrostatic chuck gaps, and a preparation method and application thereof. The main raw material of the sealant is silicone, and it may also include modified nano-silicon dioxide and other fillers. The present invention has a convenient operation process and a wide range of applications, and is applicable to gaps of any shape as long as the thickness is less than 2 mm. At the same time, the sealant has better corrosion resistance, reduces the maintenance cost of the electrostatic chuck, and prolongs its service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of semiconductor materials, and in particular to a sealant for gaps in an electrostatic chuck, and a preparation method and application thereof. Background Art

[0002] The seals of semiconductor equipment are not only required to be resistant to high temperatures and etching gases, but also have increasingly stringent requirements on their size and shape. Electrostatic chucks are used as clamping tools for silicon wafers in semiconductor processes. Electrostatic chucks are usually composed of ceramic as a dielectric layer and metal parts as a lower electrode, and the gap between the dielectric layer and the electrode is inevitable. The gap between the electrode and the dielectric on the electrostatic chucks produced by different manufacturers is also different. In actual use, corrosive gases such as plasma will remain in the gap, which will destroy the internal structure of the electrostatic chuck on the one hand, and on the other hand, there will be contaminated particles in the gap that affect the success rate of the etching process. Therefore, it is necessary to coat the gap of the electrostatic chuck with a corrosion-resistant material.

[0003] In the prior art, the patent application document with publication number CN115873359A mentioned that the use of extremely fine seals (<0.5mm) for coating can achieve good results. However, due to differences in manufacturers, batches, and models, the gap sizes of electrostatic chucks are not completely consistent, and there will be certain size differences. The gap size itself is relatively small, and even if the difference is small, it is necessary to redesign the drawings and issue the mold, which invisibly increases the workload and cost.

[0004] The present invention avoids the shortcomings of the above inventions, invents a new type of caulking technology, and invents a formula of sealant. The present invention has a convenient operation process and a wide range of applications, and is applicable to any gap of any shape as long as the thickness is less than 2 mm. At the same time, the sealant has better corrosion resistance, reduces the maintenance cost of the electrostatic chuck, and prolongs its service life. Summary of the invention

[0005] In view of the above-mentioned shortcomings of the prior art, an object of the present invention is to provide a sealant for the gap of an electrostatic chuck and a preparation method and application thereof, so as to solve the problems in the prior art.

[0006] To achieve the above-mentioned object and other related objects, one aspect of the present invention provides a sealant for the gap of an electrostatic chuck, wherein the raw materials of the sealant include the following components in parts by weight:

[0007] Silicone 100 parts

[0008] 0-15 parts of modified nano silicon dioxide;

[0009] Other fillers 0-5 parts.

[0010] The second aspect of the present invention provides a method for preparing a sealant for an electrostatic chuck gap, the method comprising blending and stirring organic silicon, modified nano-silicon dioxide, and other fillers, vacuuming and degassing in a vacuum environment, and centrifuging to obtain the sealant.

[0011] The third aspect of the present invention provides the use of the sealant for the gap of the electrostatic chuck described in the first aspect of the present invention in the gap of the electrostatic chuck.

[0012] The fourth aspect of the present invention provides an electrostatic chuck assembly, which includes an electrostatic chuck and the sealant described in the first aspect of the present invention, the electrostatic chuck includes a base, a lower electrode and a dielectric layer are stacked in sequence on the base in a direction away from the base, a gap is provided between the lower electrode and the dielectric layer, and the gap is filled with sealant.

[0013] Compared with the prior art, the present invention has the following beneficial effects:

[0014] 1. The sealant product of the present invention reduces the maintenance cost of the electrostatic chuck and is suitable for gaps of electrostatic chucks of various shapes and sizes. Before curing, it is liquid and has leveling properties, and can fill the gaps. After curing, it is solid and has a certain strength, and can well protect the adhesive layer of the electrostatic chuck;

[0015] 2. The sealant prepared by the present invention has a long operating time (>30min) and a high success rate of glue coating;

[0016] 3. The sealant product of the present invention has good corrosion resistance, is better than the existing fluorosilicone sealant, and is slightly better than FFKM rubber, and prolongs the service life of the electrostatic chuck;

[0017] 4. The sealant product of the present invention adopts a specific organosilicon, preferably modified nano-silicon oxide, mixes the modified nano-silicon oxide with the specific organosilicon, and further adjusts the ratio between the two, so that the appearance, operability, and anti-plasma corrosion performance of the obtained sealant are improved;

[0018] 5. The sealant product of the present invention improves the bonding tightness and corrosion resistance by adding titanium dioxide or lithopone.

[0019] 6. The sealant product of the present invention can be applied to the bonding between interfaces of various different materials, and has a very good bonding tightness. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a schematic diagram of the electrostatic chuck structure;

[0021] Figure 2 is a cross-sectional view of an electrostatic chuck;

[0022] Reference numerals:

[0023] 1-dielectric layer; 2-lower electrode; 3-base; 4-gap. DETAILED DESCRIPTION

[0024] Generally, materials used in the semiconductor field have very high requirements for the content of metal impurities, and the corresponding materials have very high requirements for plasma corrosion resistance. For the gap of the electrostatic chuck, it is necessary to find a sealing material that takes into account corrosion resistance, adhesion, transparency, and extended service life. After a large number of experiments, the inventors of the present invention found that by using a specific organosilicon, and further preferably coordinating with modified nano-silicon oxide, the modified nano-silicon oxide is mixed with a specific organosilicon, and the ratio between the two is further adjusted, the appearance, operability, and plasma corrosion resistance of the obtained sealant are improved. The sealant can be used for the sealing of the electrostatic chuck, protecting the adhesive between the two media, and applied to the gap of the electrostatic chuck of any shape with a thickness of less than 2 mm. On this basis, the present invention is completed.

[0025] The following describes in detail a sealant for electrostatic chuck gaps and an implementation method for its preparation and application.

[0026] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0027] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0028] Sealant for gaps in electrostatic chucks

[0029] One aspect of the present invention provides a sealant for the gap of an electrostatic chuck, the main raw material of which is organic silicon, and may also include modified nano-silicon dioxide and other fillers, such as titanium dioxide and lithopone.

[0030] The sealant for the gap of the electrostatic chuck provided by the present invention may include 100 parts of organic silicon by weight. Due to the special size of the gap 4 of the electrostatic chuck, the circumference is usually larger than 0.9m and the height is smaller than 1cm ( Figure 1 , Figure 2 The size of the gap 4 in the middle); on the other hand, the depth is generally less than 2 mm. In order to meet the cleanliness requirements, only a small amount of organic silicone with no additives and transparent and colorless appearance can be selected. The organic silicone of the present invention can be, for example, organic silicone A and organic silicone B. More specifically, organic silicone A can be, for example, organic silicone with model NX-085 of Toli Technology, and organic silicone B can be, for example, organic silicone with model DOWSIL-7091 of Dow Chemical.

[0031] The sealant for the gap of the electrostatic chuck provided by the present invention can be composed of 0 to 15 parts of modified nano silicon dioxide in parts by weight. Optionally, the weight of the modified nano silicon dioxide can be, for example, 0 to 2 parts, 2 to 10 parts, 10 to 15 parts, 0 to 3 parts, 3 to 5 parts, 5 to 8 parts, 8 to 10 parts, 10 to 15 parts, 0 to 1 part, 0 to 2 parts, 0 to 5 parts, 0 to 10 parts, 1 to 2 parts, 1 to 5 parts, 1 to 10 parts, 2 to 5 parts, 5 to 10 parts or 10-15 parts.

[0032] Among them, the modified nano silicon dioxide is obtained by modifying nano silicon dioxide. On the one hand, nano SiO2 has a relatively high activity and is easy to be hydrophilic due to the large number of silanol groups (isolated hydroxyl groups, dihydroxyl groups, and adjacent hydroxyl groups) on the surface, and is difficult to disperse and infiltrate in the organic phase; on the other hand, nano SiO2 has a very small particle size, so its specific surface area and surface energy are very large and have a high hydrophilicity, and is easy to agglomerate. In order to improve the above-mentioned problem, the present invention has surface modified nano silicon oxide. The specific modification method, for example, comprises the following steps: mixing nano silicon dioxide with a solvent and a modifier, reacting at a certain temperature, and preparing modified nano silicon dioxide after post-treatment.

[0033] Furthermore, the solvent is selected from non-polar solvents, and the non-polar solvent is selected from one or more combinations of toluene, benzene, hexane, isooctane, etc.

[0034] Furthermore, the modifier is selected from one or more combinations of organochlorosilane, silane coupling agent, alcohol compound, amine compound and the like.

[0035] Furthermore, the reaction temperature is 100° C. to 120° C. In a specific embodiment, the reaction temperature can also be 100° C. to 110° C. or 110° C. to 120° C., etc.

[0036] In a specific embodiment, a certain amount of nano-silicon dioxide is weighed and slowly added to a certain amount of toluene solution, stirring while adding the nano-silicon dioxide. After stirring evenly, the mixed solution is transferred into a three-necked flask, placed in a constant temperature water bath, and quickly stirred with a magnetic stirrer. After it is completely dispersed, a certain mass fraction of the modifier is slowly added dropwise. After the addition is completed, the temperature is gradually increased to 100°C to 120°C, condensed and refluxed, and then stirred for 3 hours, and then naturally cooled to room temperature. The mixed solution is washed with an organic solvent for multiple times and dried to obtain modified nano-silicon dioxide.

[0037] Furthermore, the mass volume ratio of nano-silicon dioxide to solvent is (0.02-0.5) g:1 mL. In a specific embodiment, the mass volume ratio of nano-silicon dioxide to solvent can also be (0.02-0.1) g:1 mL, (0.1-0.3) g:1 mL or (0.3-0.5) g:1 mL.

[0038] Furthermore, the mass ratio of nano-silicon dioxide to the modifier is (10-50): (90-50).

[0039] Further, the nano-silicon dioxide may be, for example, white carbon black. The white carbon black may be, for example, fumed white carbon black and / or precipitated white carbon black. More specifically, the fumed white carbon black may be, for example, fumed silica Evonik Aerosil 200. The precipitated white carbon black may be, for example, precipitated silica Arosil-120, precipitated silica SIPERNAT D10, and the like.

[0040] Further, the nano silicon dioxide is nano silicon dioxide powder, and its particle size can be, for example, 20nm-100nm. In some embodiments, the particle size of the nano silicon dioxide can be, for example, 20nm-40nm, 40nm-60nm, 60nm-80nm or 80nm-100nm, etc. Within this particle size range, the advantages are small particle size, large specific surface area, and strong adsorption capacity. The adsorption capacity is weakened when it exceeds 100nm, and the dispersion is poor when it is less than 20nm.

[0041] The sealant for the gap of the electrostatic chuck provided by the present invention may further include 0 to 5 parts of titanium dioxide by weight. Optionally, the titanium dioxide may be 0 to 0.1 parts, 0.1 to 5 parts, 0 to 1 parts, 1 to 3 parts or 3 to 5 parts.

[0042] The sealant for the gap of the electrostatic chuck provided by the present invention may further include 0 to 5 parts of lithopone by weight. Optionally, the lithopone may be 0 to 0.1 parts, 0.1 to 5 parts, 0.1 to 3 parts, 0 to 1 parts, 1 to 3 parts or 3 to 5 parts.

[0043] In a specific embodiment of the present invention, the raw materials of the sealant for the gap of the electrostatic chuck include the following components in parts by weight:

[0044]

[0045] In a specific embodiment of the present invention, the raw materials of the sealant for the gap of the electrostatic chuck include the following components in parts by weight:

[0046] 100 parts of silicone;

[0047] 2-10 parts of modified nano silicon dioxide;

[0048] 0.1 to 5 parts of titanium dioxide.

[0049] In a specific embodiment of the present invention, the raw materials of the sealant for the gap of the electrostatic chuck include the following components in parts by weight:

[0050] 100 parts of silicone;

[0051] 2-10 parts of modified nano silicon dioxide;

[0052] 0.1 to 5 parts of Lithopone.

[0053] The present application synthesizes modified nano-silicon oxide, and then mixes the modified nano-silicon oxide with organosilicon A, and adjusts the ratio to improve its appearance, operability, and anti-plasma corrosion performance. The organosilicon A and the modified nano-silicon oxide can be used to seal the electrostatic chuck and protect the adhesive between the two media. Organosilicon B and the modified nano-silicon oxide can adjust the operability, which can make the success rate of repairing the appearance better. And the selection and ratio of silicon oxide can adjust the appearance, transparency, and corrosion resistance of the product. In addition, the addition of titanium dioxide or lead powder also helps to improve the bonding tightness and corrosion resistance.

[0054] Preparation method of sealant for electrostatic chuck gap

[0055] The second aspect of the present invention provides a method for preparing the sealant for the gap of the electrostatic suction cup described in the first aspect of the present invention, the preparation method comprising blending and stirring silicone, modified nano-silica, and other fillers, vacuuming and degassing in a vacuum environment, and centrifuging to obtain the sealant.

[0056] In the preparation method of the sealant provided by the present invention, other fillers may be, for example, titanium dioxide, lithopone, etc.

[0057] In the preparation method of the sealant provided by the present invention, the weight proportions of the organic silicon, modified nano-silicon dioxide, and other fillers (titanium dioxide, lithopone, etc.) are as described in the first aspect of the present invention.

[0058] In the preparation method of the sealant provided by the present invention, in the blending and stirring step, the rotation speed is 40-100 rpm, and the stirring time can be, for example, 1-10 min. The blending and stirring can be performed in a centrifugal mixer, for example, until the mixture is uniformly stirred.

[0059] In the preparation method of the sealant provided by the present invention, the vacuuming step can be carried out in a vacuum dryer, for example, to a vacuum degree of ≤0.1 MPa, and the standing time can be, for example, 5-60 min. Specifically, for example, 5-15 min, 15-30 min or 30-60 min.

[0060] In the preparation method of the sealant provided by the present invention, in the centrifugation step, the blended sealant is first transferred into a rubber tube and centrifuged in a centrifuge, wherein the rotation speed is set to 1000-2000 rpm and the centrifugation time is 10-30 min.

[0061] Preferably, after the above operation is completed, the sealant is sealed and stored in an environment of 3-5°C.

[0062] application

[0063] The third aspect of the present invention provides the use of the sealant described in the first aspect of the present invention in the gap of the electrostatic chuck.

[0064] Specifically, it is applied to electrostatic chuck gaps of any shape with a thickness of less than 2 mm. For example, it can be applied to electrostatic chuck gaps with a thickness of 2 mm, 1.5 mm, 1 mm, 0.5 mm, 0.2 mm, 0.1 mm, 0.05 mm, 0.005 mm, etc.

[0065] Electrostatic chuck assembly

[0066] A fourth aspect of the present invention provides an electrostatic chuck assembly, the electrostatic chuck assembly comprising an electrostatic chuck and a sealant. Figure 1 and 2 The electrostatic chuck comprises a base 3, on which a lower electrode 2 and a dielectric layer 1 are stacked in sequence in a direction away from the base 3, a gap 4 is provided between the lower electrode 2 and the dielectric layer 1, and the gap 4 is filled with a sealant. The sealant is the sealant described in the first aspect of the present invention. The dielectric layer 1 may be an insulating ceramic.

[0067] Electrostatic chuck components can be used in integrated circuits, panel displays, optics and other devices that use electrostatic chucks.

[0068] Method for preparing electrostatic chuck assembly

[0069] A fifth aspect of the present invention provides a method for preparing an electrostatic chuck assembly, the method comprising filling a sealant into the gap 4 while the electrostatic chuck is rotating, and curing the sealant after performing a flattening process.

[0070] In the method for preparing the electrostatic chuck assembly provided by the present invention, in the step of rotating the electrostatic chuck, specifically, the electrostatic chuck is placed on an automatic turntable so that the automatic turntable rotates at a uniform speed.

[0071] In the method for preparing the electrostatic chuck assembly provided by the present invention, in the step of filling the gap with sealant, a glue gun is used to fill the gap with sealant.

[0072] In the method for preparing the electrostatic chuck assembly provided by the present invention, in the flattening step, a scraper is used to flatten the surface.

[0073] In the preparation method of the electrostatic suction cup assembly provided by the present invention, there are multiple curing methods in the curing step, such as heating curing, ultraviolet irradiation, room temperature curing, etc. Room temperature curing and heating curing are further selected in the present application. If it is room temperature curing, it needs to be placed in an environment with a humidity of 40%-80% and a temperature of 20℃-30℃ for curing; if it is heating curing, it can be constant temperature curing or program curing. Constant temperature curing, for example, can be heated and cured at a constant temperature of 100-150℃ in an oven for 10-60min, and program curing, for example, can be heated and cured at a heating rate of 5-20℃ / h to 150℃.

[0074] The beneficial effects of the present invention are further illustrated below in conjunction with embodiments.

[0075] In order to make the invention purpose, technical scheme and beneficial technical effect of the present invention clearer, the present invention is further described in detail below in conjunction with examples. However, it should be understood that the examples of the present invention are only for explaining the present invention, not for limiting the present invention, and the examples of the present invention are not limited to the examples given in the specification. The specific experimental conditions or operating conditions not specified in the examples are made under conventional conditions, or are made under the conditions recommended by the material supplier.

[0076] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present invention does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these explicitly mentioned two devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.

[0077] In the following examples, the reagents, materials and instruments used are all commercially available unless otherwise specified.

[0078] S1: Modified fumed silica Evonik Aerosil 200

[0079] Weigh 0.4g of nano-silica (Evonik Aerosil 200) and slowly add it to 20mL of toluene solution, stirring while adding nano-silica. After stirring evenly, transfer the mixed solution into a three-necked flask, put it into a constant temperature water bath, and stir it quickly with a magnetic stirrer. After it is completely dispersed, slowly add 25mL of 2wt% KH550 (γ-aminopropyltriethoxysilane or 3-aminopropyltriethoxysilane) modifier. After the addition is completed, gradually increase the temperature to 110°C, condense and reflux, then continue stirring for 3h, and then cool naturally to room temperature. Wash the mixed solution several times with organic solvents anhydrous ethanol and acetone, dry it, and obtain modified fumed silica Evonik Aerosil 200.

[0080] S2: Modified precipitated silica spectrum Arosil-120

[0081] Weigh 0.4g of nano-silica (Arosil-120) and slowly add it to 20mL of toluene solution, stirring while adding nano-silica. After stirring evenly, transfer the mixture into a three-necked flask, put it into a constant temperature water bath, and stir it quickly with a magnetic stirrer. After it is completely dispersed, slowly add 25mL of 2wt% KH550 (γ-aminopropyltriethoxysilane or 3-aminopropyltriethoxysilane) modifier. After the addition is completed, gradually increase the temperature to 110°C, condense and reflux, then continue to stir for 3h, and then cool naturally to room temperature. Wash the mixture several times with organic solvents such as anhydrous ethanol and acetone, dry it, and obtain the modified precipitated silica spectrum Arosil-120.

[0082] S3: Modified precipitated silica SIPERNAT D10

[0083] Weigh 0.4g of nano-silica (SIPERNAT D10) and slowly add it to 20mL of toluene solution, stirring while adding nano-silica. After stirring evenly, transfer the mixed solution into a three-necked flask, put it into a constant temperature water bath, and stir it quickly with a magnetic stirrer. After it is completely dispersed, slowly add 25mL of 2wt% KH550 (γ-aminopropyltriethoxysilane or 3-aminopropyltriethoxysilane) modifier. After the addition is completed, gradually increase the temperature to 110°C, condense and reflux, then continue stirring for 3h, and then cool naturally to room temperature. Wash the mixed solution several times with organic solvents such as anhydrous ethanol and acetone, and dry it to obtain modified precipitated silica SIPERNAT D10.

[0084] Silicone A is model NX-085, Tuoli Technology;

[0085] Silicone B is model DOWSIL-7091, Dow Chemical;

[0086] Fluorosilicone rubber is model SIFEL-2617, Shin-Etsu;

[0087] The perfluoroelastomer is model PFR-1055B, Solvay.

[0088] The test methods and standards are detailed in Table 1:

[0089] Table 1

[0090]

[0091]

[0092] Example 1

[0093] Weigh 100 parts of silicone A and put it into a vacuum dryer for degassing until the vacuum degree is 0.1Mpa, and leave it for 30 minutes. After the vacuum degassing is completed, move the sealant into the hose and put it into the centrifuge for centrifugation. The centrifuge speed is set to 2000rpm and the centrifugation time is 15 minutes. After the above operation is completed, seal the sealant and store it in an environment of 3-5℃.

[0094] Place the electrostatic chuck on the automatic turntable, wait for the turntable to rotate at a constant speed, use a glue gun to fill the gap with sealant, and then use a scraper to smooth the surface. Heat and cure at a constant temperature of 150℃ in an oven for 60 minutes.

[0095] Example 2

[0096] Weigh 100 parts of silicone A into a rubber cup, then add 2 parts of S1 into it, place it in a centrifugal mixer, set the speed to 100 rpm, blend and stir for 10 minutes until uniform, then place it in a vacuum dryer for degassing, pump to a vacuum degree of 0.1Mpa, and place it for 30 minutes. After the vacuum degassing is completed, move the blended sealant into a hose and place it in a centrifuge for centrifugation. Set the centrifuge speed to 2000rpm and the centrifugation time to 15 minutes. After the above operations are completed, seal and store the blended sealant in an environment of 3-5℃.

[0097] Place the electrostatic chuck on the automatic turntable, wait for the turntable to rotate at a constant speed, use a glue gun to fill the gap with sealant, and then use a scraper to smooth the surface. Heat and cure at a constant temperature of 150℃ in an oven for 60 minutes.

[0098] Example 3

[0099] Weigh 100 parts of silicone A into a rubber cup, then add 5 parts of S1 into it, place it in a centrifugal mixer, set the speed to 100 rpm, blend and stir for 10 minutes until uniform, then place it in a vacuum dryer for degassing, pump to a vacuum degree of 0.1Mpa, and place it for 30 minutes. After the vacuum degassing is completed, move the blended sealant into a hose and place it in a centrifuge for centrifugation. The centrifuge speed is set to 2000rpm and the centrifugation time is 15 minutes. After the above operations are completed, seal the blended sealant and store it in an environment of 3-5℃.

[0100] Place the electrostatic chuck on the automatic turntable, wait for the turntable to rotate at a constant speed, use a glue gun to fill the gap with sealant, and then use a scraper to smooth the surface. Heat and cure at a constant temperature of 150℃ in an oven for 60 minutes.

[0101] Example 4

[0102] Weigh 100 parts of silicone A into a rubber cup, then add 10 parts of S1 into it, place it in a centrifugal mixer, set the speed to 100 rpm, blend and stir for 10 minutes until uniform, then place it in a vacuum dryer for degassing, pump to a vacuum degree of 0.1Mpa, and place it for 30 minutes. After the vacuum degassing is completed, move the blended sealant into a hose and place it in a centrifuge for centrifugation. The centrifuge speed is set to 2000rpm and the centrifugation time is 15 minutes. After the above operations are completed, seal the blended sealant and store it in an environment of 3-5℃.

[0103] Place the electrostatic chuck on the automatic turntable, wait for the turntable to rotate at a constant speed, use a glue gun to fill the gap with sealant, and then use a scraper to smooth the surface. Heat and cure at a constant temperature of 150℃ in an oven for 60 minutes.

[0104] Example 5

[0105] Weigh 100 parts of silicone A into a rubber cup, then add 5 parts of S1 and 0.1 parts of titanium dioxide, place it in a centrifugal mixer, set the speed to 100 rpm, blend and stir for 10 minutes until uniform, then place it in a vacuum dryer for degassing, pump to a vacuum degree of 0.1Mpa, and place it for 30 minutes. After the vacuum degassing is completed, move the blended sealant into a hose and place it in a centrifuge for centrifugation. The centrifuge speed is set to 2000rpm and the centrifugation time is 15 minutes. After the above operations are completed, seal the blended sealant in an environment of 3-5℃.

[0106] Place the electrostatic chuck on the automatic turntable, wait for the turntable to rotate at a constant speed, use a glue gun to fill the gap with sealant, and then use a scraper to smooth the surface. Heat and cure at a constant temperature of 150℃ in an oven for 60 minutes.

[0107] Example 6

[0108] Weigh 100 parts of silicone A into a rubber cup, then add 5 parts of S1 and 0.1 parts of Lithopone, place in a centrifugal mixer, set the speed to 100 rpm, blend and stir for 10 minutes until uniform, then place in a vacuum dryer for degassing, pump to a vacuum degree of 0.1Mpa, and place for 30 minutes. After the vacuum degassing is completed, move the blended sealant into a hose and place in a centrifuge for centrifugation. Set the centrifuge speed to 2000rpm and the centrifugation time to 15 minutes. After the above operations are completed, seal and store the blended sealant in an environment of 3-5℃.

[0109] Place the electrostatic chuck on the automatic turntable, wait for the turntable to rotate at a constant speed, use a glue gun to fill the gap with sealant, and then use a scraper to smooth the surface. Heat and cure at a constant temperature of 150℃ in an oven for 60 minutes.

[0110] Example 7

[0111] Weigh 100 parts of silicone A into a rubber cup, then add 5 parts of S2, place it in a centrifugal mixer, set the speed to 100 rpm, blend and stir for 10 minutes until uniform, then place it in a vacuum dryer for degassing, pump to a vacuum degree of 0.1Mpa, and place it for 30 minutes. After the vacuum degassing is completed, move the blended sealant into a hose and place it in a centrifuge for centrifugation. The centrifuge speed is set to 2000rpm and the centrifugation time is 15 minutes. After the above operations are completed, seal the blended sealant and store it in an environment of 3-5℃.

[0112] Place the electrostatic chuck on the automatic turntable, wait for the turntable to rotate at a constant speed, use a glue gun to fill the gap with sealant, and then use a scraper to smooth the surface. Heat and cure at a constant temperature of 150℃ in an oven for 60 minutes.

[0113] Example 8

[0114] Weigh 100 parts of silicone A into a rubber cup, then add 5 parts of S3, place it in a centrifugal mixer, set the speed to 100 rpm, blend and stir for 10 minutes until uniform, then place it in a vacuum dryer for degassing, pump to a vacuum degree of 0.1Mpa, and place it for 30 minutes. After the vacuum degassing is completed, move the blended sealant into a hose and place it in a centrifuge for centrifugation. The centrifuge speed is set to 2000rpm and the centrifugation time is 15 minutes. After the above operations are completed, seal the blended sealant in an environment of 3-5℃.

[0115] Place the electrostatic chuck on the automatic turntable, wait for the turntable to rotate at a constant speed, use a glue gun to fill the gap with sealant, and then use a scraper to smooth the surface. Place it in an environment with a humidity of 50% and a temperature of 25°C for room temperature curing.

[0116] Example 9

[0117] Weigh 100 parts of silicone B and put it into a vacuum dryer for degassing until the vacuum degree is 0.1Mpa, and leave it for 2 minutes. After the vacuum degassing is completed, move the sealant into the hose and put it into the centrifuge for centrifugation. The centrifuge speed is set to 2000rpm and the centrifugation time is 5 minutes. After the above operation is completed, seal the sealant and store it in an environment of 3-5℃.

[0118] Place the electrostatic chuck on the automatic turntable, wait for the turntable to rotate at a constant speed, use a glue gun to fill the gap with sealant, and then use a scraper to smooth the surface. Place it in an environment with a humidity of 50% and a temperature of 25°C for room temperature curing.

[0119] Example 10

[0120] Weigh 100 parts of silicone B into a rubber cup, then add 5 parts of S1, place it in a centrifugal mixer, set the speed to 100 rpm, blend and stir for 10 minutes until uniform, then place it in a vacuum dryer for degassing, pump to a vacuum degree of 0.1Mpa, and place it for 2 minutes. After the vacuum degassing is completed, move the blended sealant into a hose and place it in a centrifuge for centrifugation. Set the centrifuge speed to 2000rpm and the centrifugation time to 5 minutes. After the above operations are completed, seal the blended sealant and store it in an environment of 3-5℃.

[0121] Place the electrostatic chuck on the automatic turntable, wait for the turntable to rotate at a constant speed, use a glue gun to fill the gap with sealant, and then use a scraper to smooth the surface. Place it in an environment with a humidity of 50% and a temperature of 25°C for room temperature curing.

[0122] Embodiment 11

[0123] Weigh 100 parts of silicone B into a rubber cup, then add 5 parts of S1 and 0.1 parts of titanium dioxide, place it in a centrifugal mixer, set the speed to 100rpm, and blend it for 10 minutes until it is uniform, then put it into a vacuum dryer for degassing, pump it to a vacuum degree of 0.1Mpa, and place it for 2 minutes. After the vacuum degassing is completed, move the blended sealant into a hose and place it in a centrifuge for centrifugation. The centrifuge speed is set to 2000rpm and the centrifugation time is 5 minutes. After the above operations are completed, seal the blended sealant and store it in an environment of 3-5℃.

[0124] Place the electrostatic chuck on the automatic turntable, wait for the turntable to rotate at a constant speed, use a glue gun to fill the gap with sealant, and then use a scraper to smooth the surface. Place it in an environment with a humidity of 50% and a temperature of 25°C for room temperature curing.

[0125] Example 12

[0126] Weigh 100 parts of silicone B into a rubber cup, then add 5 parts of S1 and 0.1 parts of Lithopone, place in a centrifugal mixer, set the speed to 100 rpm, blend and stir for 10 minutes until uniform, then place in a vacuum dryer for degassing, pump to a vacuum degree of 0.1Mpa, and place for 2 minutes. After the vacuum degassing is completed, move the blended sealant into a hose and place in a centrifuge for centrifugation. Set the centrifuge speed to 2000rpm and the centrifugation time to 5 minutes. After the above operations are completed, seal and store the blended sealant in an environment of 3-5℃.

[0127] Place the electrostatic chuck on the automatic turntable, wait for the turntable to rotate at a constant speed, use a glue gun to fill the gap with sealant, and then use a scraper to smooth the surface. Place it in an environment with a humidity of 50% and a temperature of 25°C for room temperature curing.

[0128] Comparative Example 1

[0129] Fluorosilicone sealant was filled into the gap of the electrostatic chuck and placed in an environment with a humidity of 50% and a temperature of 25°C for room temperature curing.

[0130] Comparative Example 2

[0131] Fill the gap of the electrostatic chuck with fluorosilicone sealant and heat and cure it in an oven at 150°C for 60 minutes.

[0132] Comparative Example 3

[0133] The first stage vulcanization temperature is 170℃, the time is 20min; the second stage vulcanization temperature is 230℃, the time is 4 hours.

[0134] Table 2 shows the performance test data of various embodiments and comparative examples.

[0135] Table 2

[0136]

[0137]

[0138]

[0139] As shown in Table 2, the comparative examples use fluorosilicone rubber and perfluoroether rubber as the base rubber, and the examples use silica gel as the base rubber. S1 is modified fumed silica Evonik Aerosil 200, S2 is modified precipitated silica Arosil-120, and S3 is modified precipitated silica SIPERNAT D10. Silicone A is heated and cured, and silicone B is room temperature cured. The performance parameters shown in Table 1, the higher the value, the better the performance.

[0140] It can be seen from Comparative Examples 1, 2, 3 and Examples 1 and 9 that the overall effect of organic silicon sealant is better than the performance of sealant with fluorosilicone and FFKM as the base glue. The strength of fluorosilicone sealant is very poor, the bonding tightness of FFKM is very poor, and the corrosion resistance of both is also poor, and neither has an ideal service life. However, organic silicon has achieved better performance parameters and corrosion resistance without any additives.

[0141] It can be seen from Example 1 and Example 9 that the effects of heating curing and room temperature curing are basically the same, but heating curing is worse than room temperature curing in terms of adaptability and ease of processing, but not as good as room temperature curing in terms of perfect adaptability and material cost. The comprehensive scores are both 29.

[0142] As can be seen from Examples 1-4, the addition of S1 has improved the strength and appearance to a certain extent, but when the amount is too much, the processing difficulty increases, and higher requirements are put forward for the blending technology. The corrosion resistance gradually increases with the increase of the amount of silicon dioxide. The comprehensive scores of the modulated silicone A are all above 30 points.

[0143] It can be seen from Examples 3, 5 and 6 that the bonding tightness and corrosion resistance are improved after adding titanium dioxide or lithopone, while other properties remain unchanged.

[0144] It can be seen from Example 1, Example 3, Example 7 and Example 8 that the addition effect of precipitated silica is better than that of gas phase silica, but the addition effect of both gas phase method and precipitation method is better.

[0145] It can be found from the above examples that both fumed silica and precipitated silica have excellent effects on electrostatic chuck sealants, and precipitated silica is better than fumed silica. The bonding tightness and corrosion resistance are improved after adding titanium dioxide or lead powder. At the same time, room temperature curing and heating curing also have better effects, and the effect of heating curing is better than room temperature curing. In specific situations, whether to use room temperature curing type or heating curing type silicone can be selected according to the temperature resistance of the sample being constructed, or according to the existing equipment.

[0146] In summary, the present invention effectively overcomes various shortcomings of the prior art and has high industrial utilization value.

[0147] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and evolutions of the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A sealant for the gap of an electrostatic chuck, characterized in that: The sealant comprises the following components in parts by weight: Silicone 100 parts 2-10 parts of modified nano silicon dioxide; Other fillers 0-5 parts; The modified nano-silicon dioxide modification method comprises: mixing nano-silicon dioxide with a solvent and a modifier, reacting at a certain temperature, and preparing the modified nano-silicon dioxide after post-treatment; the particle size of the nano-silicon dioxide powder is 20nm-100nm; the mass ratio of the nano-silicon dioxide to the modifier is (10-50): (90-50); The organosilicon is NX-085 or DOWSIL-7091 organosilicon; The modifier is a silane coupling agent; The other fillers are selected from titanium dioxide and / or lithopone, the weight portion of the titanium dioxide is 0.1 to 5 parts, and the weight portion of the lithopone is 0.1 to 5 parts.

2. The sealant for the gap of an electrostatic chuck according to claim 1, characterized in that: The appearance of the organic silicone is colorless and transparent.

3. The sealant for the gap of an electrostatic chuck according to claim 1, characterized in that: Also includes any one or more of the following features: B1) the nano silicon dioxide is white carbon black; B2) the nano silicon dioxide is nano silicon dioxide powder; B3) the solvent is selected from a non-polar solvent, and the non-polar solvent is selected from a combination of one or more of toluene, benzene, hexane, and isooctane; B4) the reaction temperature of the reaction is 100°C to 120°C; B5) The mass volume ratio of the nano-silicon dioxide to the solvent is (0.02-0.5) g:1 mL.

4. The sealant for the gap of an electrostatic chuck according to claim 3, characterized in that: The white carbon black is fumed white carbon black and / or precipitated white carbon black.

5. The method for preparing a sealant for electrostatic chuck gaps according to any one of claims 1 to 4, the method comprising blending and stirring organic silicon, modified nano-silicon dioxide, and other fillers, vacuuming and degassing in a vacuum environment, and centrifuging to obtain the sealant.

6. The method for preparing a sealant for an electrostatic chuck gap according to claim 5, characterized in that: Also includes any one or more of the following features: D1) In the blending and stirring step, the rotation speed is 40-100 rpm and the stirring time is 1-10 min; D2) In the vacuuming step, the vacuum is evacuated to a degree of ≤0.1 MPa, and the standing time is 5-60 min; D3) In the centrifugation step, the speed is set to 1000-2000 rpm and the centrifugation time is 10-30 min; D4) sealing and storing the prepared sealant in an environment of 3-5°C.

7. Use of the sealant for the gap of an electrostatic chuck as claimed in any one of claims 1 to 4 in the gap of an electrostatic chuck.

8. An electrostatic chuck assembly, characterized in that: The electrostatic chuck assembly comprises an electrostatic chuck and a sealant as claimed in any one of claims 1 to 4, wherein the electrostatic chuck comprises a base (3), a lower electrode (2) and a dielectric layer (1) are sequentially stacked on the base (3) in a direction away from the base (3), a gap (4) is provided between the lower electrode (2) and the dielectric layer (1), and the gap (4) is filled with sealant.

Citation Information

Patent Citations

  • Food-grade self-leveling temperature-resisting sealant and preparation method thereof

    CN109306258A

  • Fluororubber superfine sealing element for protecting gap of electrostatic chuck

    CN115873359A

Cited By

  • Fluorine-containing elastomer toughened crystalline fluorine-containing polymer and application of fluorine-containing elastomer toughened crystalline fluorine-containing polymer in sealing element

    CN120865660A

  • Fluoroelastomer toughened crystalline fluoropolymers and seal applications thereof

    CN120865660B